Wind action on flat roofs - Lipecki, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper deals with the wind action on flat roofs of rectangular shapes which can be considered for medium-rise and high-rise buildings. Distributions of mean pressure coefficient Cp on flat roofs were measured. All analyses were based on model measurements which had been performed in the boundary layer wind tunnel in Wind Engineering Laboratory of Cracow University of Technology. Vertical, fixed in the floor of the wind tunnel on the turn table rectangular prisms of the ratio of cross-section dimensions 1:2 and 1:4 were investigated. Measurements were carried out for the angle of wind attack in the range 0°-90°, every 15°. The influence of the wind structure on pressures was investigated in six different cases of the approaching wind.